Hubungan Senam Tera Terhadap Kadar Gula Darah Lansia - Mohammad Noval Baghaskara; Noortje Anita Kumaat (Lembaga Pengembangan Kinerja Dosen, 2024)
The aging process is a natural thing experienced by every human being, every individual will experience a process of life development from initially being a toddler then becoming a child, teenager, adult and then becoming an elderly person. Terra exercise can increase the burning of blood sugar in the body so that blood sugar levels become normal. This research is a descriptive quantitative research with a correlational approach. This research was conducted on November 15 2023, at the Buduran Village Hall, Sidoarjo Regency. Before and after the Tera exercise, blood sugar is measured with a glucometer. This research was analyzed using a correlation test according to Spearman Rank with SPSS 2023. This research obtained a sample of 30 people. The average blood sugar level before tera exercise was 134.93 mg/dL and after being given tera exercise treatment it decreased to 120.93 mg/dL with a p value of 0.005. Based on the research conducted, it can be concluded that there is a significant relationship between tera exercise and the blood sugar levels of the elderly in the elderly posyandu Buduran Village, Sidoarjo Regency.